Improving activity of Ni3P/Mn hybrid film via electrochemical tuning for water splitting under simulated industrial environment. (20th November 2019) - Tan, Ya; Li, Qing; Che, Qijun; Chen, Xinhong; Xu, Xi; Chen, Yashi
Abstract: The design of large-scale and stable bifunctional electrocatalyst with excellent activities at large current density is one of the powers to promote the development of industrial water electrolysis. In this work, a super-hydrophilic non-noble metal electrocatalyst, Ni3 P/MnOOH, was prepared by electrochemical tuning on Ni3 P/Mn precursor that was grown firstly on 3D porous conductive nickel foam substrate by electrodeposition. The Ni3 P/MnOOH hybrid catalyst displays high electrocatalytic activity that requires a low overpotential of 268 mV and 341 mV at 1000 mA cm −2 for hydrogen evolution reaction and oxygen evolution reaction in simulated industrial environment, respectively. Remarkably, an alkaline electrolyzer constucted by Ni3 P/MnOOH hybrid electrode as the anode and cathode only require a cell voltage of 1.53 V at 10 mA cm −2 with prominent stability under above half-reaction condition. This work not only improves the OER activity of catalysts with good HER performance, but also provides a broad prospect for its application in large-scale electrolytic water.